Potensi Energi Surya Sebagai Sumber Pembangkit Tenaga Listrik untuk Penerangan Rumah 450 Watt - Rohmah, Nofia; Sudarti (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2021)
The use of solar energy as a source of electricity generation for lighting a 450 watt house can help reduce the burden of electricity financing. Using a descriptive research method, data on the use of electric power at night were obtained from the house in Kampung Persil Nyeoran, Blok K.12, Kecamatan Jatiroto, Kabupaten Lumajang, Jawa Timur, Indonesia. Data collection was carried out in March 2021. After collecting the data it can be concluded that for the construction of a 450 watt simple home lighting PLTS, 6 solar panels with a capacity of 100 Wp are needed, 5 batteries with a capacity of 12 V 100 Ah, 1 inverter with a capacity of 3000 W and 1 charger. controller capacity of 10 A.